2013
DOI: 10.1007/s00404-013-3065-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the outcomes of laparoscopic hysterectomy for normal and enlarged uterus (>280 g)

Abstract: In our study, we compared the outcomes of LH in patients with large uterus measuring up to 700 g. and patients with normal uterus, and we achieved successful results by making minor changes in the operation technique and performing diagnostic CYS at the end of the operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 19 publications
2
17
0
Order By: Relevance
“…Notably, as well explained by Wu KY et al [9] and Yazucan et al [10], and also the case in our patient, the trocars positioning on the basis of the uterine size was the first and valued as the most important step affecting the laparoscopic surgery outcome, in addition to the choice of instruments and the experience and the harmony of the operating team [1, 11]. Furthermore, the techniques that we found helpful in completing the procedure through a minimally invasive approach were changing the trocars sites of the laparoscope throughout the procedure for better visualization (in fact, in the present case we started with the trocar positioned near the xiphoid process and then continued with umbilical access), and as specified by Yazucan et al [10] the ability to suspend from the pelvic floor the uterus through a skillful use of the uterine manipulator thus obtaining also both the best inspection of the ureter projections and a clear visualization of the vesico-uterine fold that aids to avoid potential bladder injury.…”
Section: Discussionmentioning
confidence: 59%
“…Notably, as well explained by Wu KY et al [9] and Yazucan et al [10], and also the case in our patient, the trocars positioning on the basis of the uterine size was the first and valued as the most important step affecting the laparoscopic surgery outcome, in addition to the choice of instruments and the experience and the harmony of the operating team [1, 11]. Furthermore, the techniques that we found helpful in completing the procedure through a minimally invasive approach were changing the trocars sites of the laparoscope throughout the procedure for better visualization (in fact, in the present case we started with the trocar positioned near the xiphoid process and then continued with umbilical access), and as specified by Yazucan et al [10] the ability to suspend from the pelvic floor the uterus through a skillful use of the uterine manipulator thus obtaining also both the best inspection of the ureter projections and a clear visualization of the vesico-uterine fold that aids to avoid potential bladder injury.…”
Section: Discussionmentioning
confidence: 59%
“…The study group comprised patients who were found to have adenomyotic lesions in the postoperative histopathologic examination of tissue sections, and the control group comprised patients who did not have any adenomyotic lesions. All patients underwent bimanual pelvic examination, transvaginal ultrasonography (USG), cervico-vaginal smear, and endometrial tissue sampling in order to rule out the presence of any malignancy before surgery (9). The patients that had undergone cesarean section, hysterotomy, adnexal surgery, appendectomy, rectosigmoid surgery, or similar surgery in the pelvic area in the past were considered to have a positive history of pelvic surgery.…”
Section: Methodsmentioning
confidence: 99%
“…The anesthesiologist recorded the operation time based on the patient followup forms. Delta hemoglobin (Hb) was defined as the difference between preoperative and postoperative Hb levels (9). A pelvic drainage system was placed before the completion of surgery in some patients, if deemed necessary by the attending surgeon.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations